Induction of labour at or near term for suspected fetal macrosomia - Boulvain, Michel; Irion, Olivier; Dowswell, Therese; Thornton, Jim (Wiley, 2016)
Background: Women with a suspected large-for-dates fetus or a fetus with suspected macrosomia (birthweight greater than 4000 g) are at risk of operative birth or caesarean section. The baby is also at increased risk of shoulder dystocia and trauma, in particular fractures and brachial plexus injury. Induction of labour may reduce these risks by decreasing the birthweight, but may also lead to longer labours and an increased risk of caesarean section. Objectives: To assess the effects of a policy of labour induction at or shortly before term (37 to 40 weeks) for suspected fetal macrosomia on theway of giving birth and maternal or perinatal morbidity. Search methods: We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (31 January 2016), contacted trial authors and searched reference lists of retrieved studies. Selection criteria: Randomised trials of induction of labour for suspected fetal macrosomia. Data collection and analysis: Review authors independently assessed trials for inclusion and risk of bias, extracted data and checked them for accuracy. We contacted study authors for additional information. For key outcomes the quality of the evidence was assessed using the GRADE approach. Main results: We included four trials, involving 1190 women. It was not possible to blind women and staff to the intervention, but for other ’Risk of bias’ domains these studies were assessed as being at low or unclear risk of bias.Compared to expectant management, there was no clear effect of induction of labour for suspected macrosomia on the risk of caesarean section (risk ratio (RR) 0.91, 95% confidence interval (CI) 0.76 to 1.09; 1190 women; four trials, moderate-quality evidence) or instrumental delivery (RR 0.86, 95% CI 0.65 to 1.13; 1190 women; four trials, low-quality evidence). Shoulder dystocia (RR 0.60, 95% CI 0.37 to 0.98; 1190 women; four trials, moderate-quality evidence), and fracture (any) (RR 0.20, 95% CI 0.05 to 0.79; 1190 women; four studies, high-quality evidence) were reduced in the induction of labour group. There were no clear differences between groups for brachial plexus injury (two events were reported in the control group in one trial, low-quality evidence). There was no strong evidence of any difference between groups for measures of neonatal asphyxia; low five-minute infant Apgar scores (less than seven) or low arterial cord blood pH (RR 1.51, 95% CI 0.25 to 9.02; 858 infants; two trials, low-quality evidence ; and, RR 1.01, 95% CI 0.46 to 2.22; 818 infants; one trial, moderate-quality evidence, respectively). Mean birthweight was lower in the induction group, but there was considerable heterogeneity between studies for this outcome (mean difference (MD) -178.03 g, 95% CI -315.26 to -40.81; 1190 infants; four studies; I= 89%). In one study with data for 818 women, third- and fourth-degree perineal tears were increased in the induction group (RR 3.70, 95% CI 1.04 to 13.17). For outcomes assessed using GRADE, we based our downgrading decisions on high risk of bias from lack of blinding and imprecision of effect estimates. Authors’ conclusions: Induction of labour for suspected fetal macrosomia has not been shown to alter the risk of brachial plexus injury, but the power of the included studies to show a difference for such a rare event is limited. Also antenatal estimates of fetal weight are often inaccurate so many women may be worried unnecessarily, and many inductions may not be needed. Nevertheless, induction of labour for suspected fetal macrosomia results in a lower mean birthweight, and fewer birth fractures and shoulder dystocia. The unexpected observation in the induction group of increased perineal damage, and the plausible, but of uncertain significance, observation of increased use of phototherapy, both in the largest trial, should also be kept in mind. Findings from trials included in the review suggest that to prevent one fracture it would be necessary to induce labour in 60 women. Since induction of labour does not appear to alter the rate of caesarean delivery or instrumental delivery, it is likely to be popular with many women. In settings where obstetricians can be reasonably confident about their scan assessment of fetal weight, the advantages and disadvantages of induction at or near term for fetuses suspected of being macrosomic should be discussed with parents. Although some parents and doctors may feel the evidence already justifies induction, others may justifiably disagree. Further trials of induction shortly before term for suspected fetal macrosomia are needed. Such trials should concentrate on refining the optimum gestation of induction, and improving the accuracy of the diagnosis of macrosomia.